The Relationship Between Age and Parity With The Incidence of Preeclampsia - Darwati Darwati; Rifzul Maulina (International Journal of Public Health, 2025)
Preeclampsia is hypertension at 20 weeks of gestation or after delivery with blood pressure ≥ 140/90 mmHg measured twice with an interval of 4 hours accompanied by proteinuria of 300 mg of protein in the urine for 24 hours. The incidence of preeclampsia in developing countries is approximately seven times higher than in developed countries (an average of 2.8% of live births 0.4%). Preeclampsia affects 5-8% of all pregnancies, and causes many complications in the mother and fetus. Age under 20 years and over 35 years is also called a high-risk age for experiencing pregnancy complications while at parity 2-3, and birth spacing > 5 years. Birth spacing is a risk factor for preeclampsia and high-risk pregnancies.